تأثير الإصلاحات الاقتصادية في الجزائر على تحقيق أهداف السياسة النقدية خلال الفترة (1990-2014). - بن جميل, أ. هناء (Recherches économiques et managériales; Vol. 19 (2016): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (JUIN), 2016)
إن الأزمات والاختلالات التي عرفها الاقتصاد الجزائري خلال سنوات الثمانينات والتي امتدت آثارها حتى مطلع التسعينات، فضلا عن رغبة الجزائر في مواكبة النظام الاقتصادي العالمي الذي فرض عليها حتمية إعادة النظر في توجهها ورسم سياسات اقتصادية أكثر فاعلية ونجاعة في تحقيق الأهداف العامة لأي دولة كانت، كل هذا جعل الحكومة الجزائرية ملزمة بالقيام بعدد من الإجراءات والإصلاحات بعضها ذاتية وأخرى بمساندة مؤسسات النقد الدولية، وذلك قصد إعادة تأهيل ركائز الاقتصاد الوطني ككل.    ومن أجل ذلك فقد تبنت السلطات النقدية في الجزائر مسؤولية المحافظة على التوازنات النقدية على المستويين الداخلي والخارجي من خلال إصدار قوانين وتشريعات كان هدفها توفير الجو المناسب لإنعاش الاقتصاد الوطني وتحريره بالاعتماد على آليات السوق والحد من دور الدولة في الحياة الاقتصادية. الكلمات المفتاحية : الإصلاحات الاقتصادية، الأهداف النهائية للسياسة الاقتصادية، التوازن الاقتصادي، الاقتصاد الجزائري. Abstract :    The crises and imbalances that occurred to the Algerian economy during the years of the eighties, and which its severe effects lasted until the early nineties, as well as the desire of Algeria to keep pace with the global economic system that imposed on it the inevitability of reconsidering its direction and draw more effective and efficient economic policies to achieve the general objectives of any country have obliged the Algerian government to carry out a number of actions and reforms (some on its own and others with the support of international monetary institutions) in order to rehabilitate the pillars of the national economy as a whole.   For such purposes, the Algerian monetary authorities have claimed responsibility for maintaining cash balances on the internal and external levels through the issuance of laws and legislation that were aimed at providing the right atmosphere for the recovery of the national economy, and freeing it through the reliance on market mechanisms and reducing the role of the government in economic life. Key words : economic reforms, the overall objectives of the economic policy, economic balance, the Algerian economy.